Answer:
b
Step-by-step explanation:
the only one that has a cop of 15 is b
The two ordered pairs to show that the equation y = 15x represents the data are (1, 15) and (2, 30) option (B) is correct.
What is a linear equation?It is defined as the relation between two variables, if we plot the graph of the linear equation we will get a straight line.
If in the linear equation, one variable is present, then the equation is known as the linear equation in one variable.
It is given that:
The linear equation is:
y = 15x
Plug x = 1
y = 15
Plug x = 2
y = 30
The two points are (1, 15) and (2, 30) which lie on the equation of the line y = 15x
Thus, the two ordered pairs to show that the equation y = 15x represents the data are (1, 15) and (2, 30) option (B) is correct.
Learn more about the linear equation here:
brainly.com/question/11897796
#SPJ2
An 18 fluid ounce bottle of lotion costs $10.99, what is the price per fluid ounce?
35
Step-by-step explanation:
6 sided die is rolled. Then a 3 colored spinner is spun. Possible outcomes for each event are 1,2,3,4,5,and 6. for the 6 sided die and red, blue, and yellow for the 3 color spinner. Identify sample space.
S = {1R, 2R, 2R, 4R, 5R, 6R, 1B, 2B, 3B, 4B, 5B, 6B, 1Y, 2Y, 3Y, 4Y, 5Y, 6Y}
Step-by-step explanation:
As there are 6 outcomes of die and 3 outcomes for spinner, the total sample space will have following elements:
n(S) = 6*3 = 18
Each outcome of die will combined with either of the colors
Let R stand for red color
Let B be for blue color
Let Y be for yellow color
So, the outcomes will be:
S = {1R, 2R, 2R, 4R, 5R, 6R, 1B, 2B, 3B, 4B, 5B, 6B, 1Y, 2Y, 3Y, 4Y, 5Y, 6Y}
Keywords: Sample space, Probability
Learn more about sample space at:
brainly.com/question/12884373brainly.com/question/12896802#LearnwithBrainly
please solve with working much appreciated
Answer:
Length n = 5 cm
Step-by-step explanation:
Given:
Each angle measure is of 60° for the triangle given in the figure.
Equilateral Triangle:
If all the angles measure of the triangle is 60° then the triangle is said to be an Equilateral Triangle.
Therefore, the triangle given in the figure is an Equilateral Triangle.
Another property of an Equilateral Triangle is
All the Three sides of an equilateral triangles are equal.
Here,
measure of each angle is 60° ...... { Given}
length of one side = 5 cm ........{Given}
∴ Length n = 5 cm
A triangle has vertices at (1, 1), (1, 4), and (-3, 4).
What are the coordinates of the circumcenter?
A. (-1, 2.5)
B (-1/3, 3)
C (0, 3)
D (1, 4)
Answer:
option A (-1, 2.5) is correct
Step-by-step explanation:
Given
Let A(1, 1)
Let B(1, 4)
Let C(-3, 4)
Let coordinates of the circumcenter is (x, y)
Using distance formula
[tex]OA = OB[/tex]
[tex]OA^{2}=OB^{2}[/tex]
[tex](x-1)^{2}+(y-1)^{2} =(x-1)^{2}+(y-1)^{4}[/tex]
[tex]x^{2} +1-2x+y^{2} +1-2y=x^{2} +1-2x+y^{2} +16-8y[/tex]
[tex]8y-2y=16-1[/tex]
[tex]y=\frac{15}{6}[/tex]
[tex]y=2.5[/tex]
[tex]OA = OC[/tex]
[tex]OA^{2}=OC^{2}[/tex]
[tex](x-1)^{2}+(y-1)^{2} =(x-(-3))^{2}+(y-4)^{4}[/tex]
[tex](x-1)^{2}+(y-1)^{2} =(x+3)^{2}+(y-4)^{4}[/tex]
[tex]x^{2} +1-2x+y^{2} +1-2y=x^{2} +9+6x+y^{2} +16-8y[/tex]
[tex]-6x-2y-2x+8y=25-2[/tex]
put the y value in this equation
[tex]-8x+6\times\frac{15}{6} = 23[/tex]
[tex]-8x=23-15\\-8x=8\\x=-1[/tex]
So the coordinates of the circumcenter is (1, 2.5)
Midpoints: AB (1, 2.5), BC (-1, 4). Perpendicular bisectors: AB (y = 2.5), BC (x = -1). Intersection at (-1, 2.5), hence circumcenter is (-1, 2.5).
So, the correct answer is A. (-1, 2.5).
To find the circumcenter of a triangle, we can use the following steps:
1. Find the midpoints of two sides of the triangle.
2. Calculate the slopes of the perpendicular bisectors of those sides.
3. Use the midpoints and slopes to find the equations of the perpendicular bisectors.
4. Find the point of intersection of the perpendicular bisectors, which is the circumcenter.
Let's begin:
Given vertices of the triangle:
A (1, 1)
B (1, 4)
C (-3, 4)
1. Finding the midpoints of sides AB and BC:
Midpoint of AB = ((x1 + x2) / 2, (y1 + y2) / 2)
Midpoint of BC = ((x2 + x3) / 2, (y2 + y3) / 2)
Midpoint of AB = ((1 + 1) / 2, (1 + 4) / 2) = (1, 2.5)
Midpoint of BC = ((1 + (-3)) / 2, (4 + 4) / 2) = (-1, 4)
2. Calculate the slopes of the sides AB and BC:
Slope of AB = (y2 - y1) / (x2 - x1)
Slope of BC = (y3 - y2) / (x3 - x2)
Slope of AB = (4 - 1) / (1 - 1) = 3 / 0 (undefined slope)
Slope of BC = (4 - 4) / (-3 - 1) = 0 / -4 = 0
The slope of AB is undefined because the difference in x-coordinates is zero, meaning it's a vertical line. For a perpendicular bisector, we need to take the negative reciprocal of this slope.
3. Calculate the negative reciprocals of the slopes of AB and BC:
Negative reciprocal of undefined slope = 0
Negative reciprocal of zero slope = undefined
4. Equations of the perpendicular bisectors:
For AB: The perpendicular bisector passes through the midpoint (1, 2.5) and has a slope of 0.
Using the point-slope form of a line equation: y - y1 = m(x - x1)
y - 2.5 = 0(x - 1)
y = 2.5
For BC: The perpendicular bisector passes through the midpoint (-1, 4) and has an undefined slope (vertical line).
So, the equation is x = -1.
Now, we find the point of intersection of the perpendicular bisectors.
The point of intersection is the circumcenter.
Since the perpendicular bisectors intersect at (-1, 2.5), which is the midpoint of AB, the circumcenter is at (-1, 2.5).
So, the correct answer is A. (-1, 2.5).
33 divided by 2 long division
Answer:
16
Step-by-step explanation:
Step 1: Start by setting it up with the divisor 2 on the left side and the dividend 32 on the right side.
Step 2: The divisor (2) goes into the first digit of the dividend (3) 1 time(s). therefore, put 1 on top.
Step 3: Multiply the divisor by the result in the previous step (2 x 1 = 2) and write that answer below the dividend.
Step 4: Subtract the result in the previous step from the first digit of the dividend (3-2=1) and write the answer below.
Step 5: Move down the 2nd digit of the dividend (2)
Step 6: The divisor (2) goes on into the bottom number (12), 6 time(s). Therefore, put 6 on top.
Step 7: Multiply the divisor by the result in the previous step (2 x 6 = 12) and write that answer at the bottom.
Step 8: Subtract the result in the previous step from the number written above it. (12-12=0) and write the answer at the bottom.
That is it.
After Dividing 33 by 2 using long division method we get,
quotient = 16 and remainder = 1
Here we have to divide,
33 by 2 through long division method,
Since we know that,
In mathematics, long division is the procedure of dividing big numbers into smaller groups or sections. It is beneficial to divide a difficulty into small and straightforward steps. Dividends, divisors, quotients, and remainders are all part of the long divisions. The dividend in a long division problem is the enormous number that is divided by another integer known as the divisor. The quotient is the outcome of the division, while the remainder is the extra quantity that cannot be divided.
Therefore, proceed the long division,
2 ) 33 ( 16
- 2
_____
1 3
- 1 2
________
1
Hence, After long division we get,
quotient = 16 and remainder = 1
To learn more about division visit:
https://brainly.com/question/2273245
#SPJ6
Richard design a great new hotel is hotel is tallest in the city it has 58 floors each floor has 18 room each room has two TV how many TVs are in his whole hotel
There are 2088 TVs in his whole hotel.
Step-by-step explanation:
No. of floors = 58
No. of rooms = 18 per floor
Total rooms = No. of floors * No. of rooms per floor
[tex]Total\ rooms = 58*18\\Total\ rooms=1044[/tex]
As every room has two TVs, therefore,
Total TVs = Total rooms * 2
[tex]Total\ TVs=1044*2\\Total\ TVs=2088[/tex]
There are 2088 TVs in his whole hotel.
Keywords: multiplication
Learn more about multiplication at:
brainly.com/question/3306327brainly.com/question/3375830#LearnwithBrainly
A floor is covered by 800 tiles measuring 10 cm squared. how many square tiles of side 8 cm would be needed to cover the same floor.
Answer:
125tiles
Step-by-step explanation:
800*10=8000
8000/64=125
9x + 9 + 2x - 7(3 + x) =
Answer:
4x-12 or 4(x-3)
Step-by-step explanation:
9x+9+2x-7(3+x)
9x+2x+9-21-7x
11x-12-7x
11x-7x-12
4x-12
Find 3 consecutive even numbers where the product of the smaller two numbers is 64
less than the square of the largest number.
Answer:
8
Step-by-step explanation:
Answer:
8,10 and 12
Step-by-step explanation:
The numbers are
(x-2)* (x-4) = x^ -64
Diistributive
x^-4x-2x+8 = x^-64
Subtract x^ on both sides (It will be cancelled)
-6x+8 = -64
Subtract 8 on both sides
-6x=-72
Divide both sides by -6
x=12
12-2=10
12-4=8
8*10=80 12*12=144 144-80=64
80+64=144
If two dice are thrown, and you sum the digits. What number has the highest probability of appearing?
Answer:
7 has the highest probability
Explanation:
When two dices are rolled simultaneously,
The possible outcomes are:
{1,1}, {1,2}, {1,3}, {1,4}, {1,5}, {1,6}
{2,1}, {2,2}, {2,3}, {2,4}, {2,5}, {2,6}
{3,1}, {3,2}, {3,3}, {3,4}, {3,5}, {3,6}
{4,1}, {4,2}, {4,3}, {4,4}, {4,5}, {4,6}
{5,1}, {5,2}, {5,3}, {5,4}, {5,5}, {5,6}
{6,1}, {6,2}, {6,3}, {6,4}, {6,5}, {6,6}
The sum of digits are
1 2 3 4 5 6 7
2 3 4 5 6 7 8
3 4 5 6 7 8 9
4 5 6 7 8 9 10
5 6 7 8 9 10 11
6 7 8 9 10 11 12
It is noted that 7 is common in every series,
therefore, 7 has the highest probability
Which recursive formula can be used to generate the sequence shown, where f(1) = 9.6 and n > 1?
9.6, –4.8, 2.4, –1.2, 0.6, ...
f(n + 1) = –0.5f(n)
f(n + 1) = 0.5f(n)
f(n + 1) = f(0.5n)
f(n + 1) = f(–0.5n)
Answer:
f(n + 1) = –0.5f(n)
Step-by-step explanation:
The terms 9.6, –4.8, 2.4, –1.2, 0.6 alternate negative and positive. This means they must have a negative rate of change (because multiplying with negatives give both positive and negative numbers).
This narrows it down to:
f(n + 1) = –0.5f(n)
f(n + 1) = f(–0.5n)
Substitute f(n) for f(1)=9.6.
f(n + 1) = –0.5(n)
f(1 + 1) = –0.5(1)
f(2) = –0.5(9.6)
f(2) = -4.8
Since the second term is -4.8, f(n + 1) = –0.5f(n) is the recursive formula.
Answer:
it is f(n + 1) = –0.5f(n)
Step-by-step explanation:
I just took it on edge 2020
Please simplify.
[tex]\frac{3c^{8} }{12c^{12} }[/tex]
A. [tex]\frac{c^{20} }{4}[/tex]
B. [tex]\frac{1}{4c^{4} }[/tex]
C. [tex]\frac{c^{4} }{4}[/tex]
D. [tex]\frac{4}{c^{4} }[/tex]
Answer:
B) 1/4c^4
Step-by-step explanation:
Because 3/12=1/4 and c^8/c^12=1/c^4.
What is the quotient StartFraction 15 p Superscript negative 4 Baseline q Superscript negative 6 Baseline Over negative 20 p Superscript negative 12 Baseline q Superscript negative 3 Baseline EndFraction in simplified form? Assume p not-equals 0, q not-equals 0. Negative StartFraction 3 p Superscript 8 Baseline Over 4 q cubed EndFraction Negative StartFraction 3 Over 4 p Superscript 16 Baseline q Superscript 9 Baseline EndFraction Negative StartFraction p Superscript 8 Baseline Over 5 q cubed EndFraction Negative StartFraction 1 Over 5 p Superscript 16 Baseline q Superscript 9 Baseline EndFraction
can be simplified to
[tex]-\frac{3p^8}{4q^3}[/tex]
Hopes this helps
if not then I'm sorrr
The quotient in simplified form for \(\frac{15p^{-4}q^{-6}}{-20p^{-12}q^{-3}}\) is \(-\frac{3p^8}{4q^3}\). This is found by dividing the numerical coefficients and subtracting the exponents for variables of the same base (negative exponents indicate reciprocals).
Explanation:To find the quotient in simplified form for \(\frac{15p^{-4}q^{-6}}{-20p^{-12}q^{-3}}\), we perform division of the coefficients (15 divided by -20) and subtraction of the exponents for variables with the same base (p's and q's exponents) according to the rules of exponents. First, simplify the numerical coefficients:
\(\frac{15}{-20} = -\frac{3}{4}\)
Now, subtract the exponents for p (applying the formula x^p \cdot x^q = x^{(p+q)}):
\(p^{-4} - p^{-12} = p^{-4 + 12} = p^8\)
Next, apply the same process to the exponents of q:
\(q^{-6} - q^{-3} = q^{-6 + 3} = q^{-3}\)
Combine the results to get the simplified quotient:
\(-\frac{3}{4} × p^8 × q^{-3}\)
Remember that a negative exponent indicates a reciprocal, so we can write \(q^{-3}\) as \(\frac{1}{q^3}\). Therefore, the final answer is:
\(-\frac{3p^8}{4q^3}\)
Learn more about Simplifying Quotients with Exponents here:https://brainly.com/question/29771176
#SPJ3
Walter asks to borrow $5 from Sharon on Monday, and another $8 on Tuesday. If he pays back $6 on Wednesday and borrows another $5 on Thursday, how much does he still owe Sharon on Friday
Answer:
$12 is owed
Step-by-step explanation:
5 + 5 + 8 = 18
18 - 6 = 12
2 1⁄100 kilometers = decimeters
Answer:
20100 decimeters
Step-by-step explanation:
1 kilometer=10,000 decimeters
2 1/100=201/100
201/100*10,000=20100
Answer:
[tex]\large\boxed{2\dfrac{1}{100}\ kilometers=20100\ decimeters}[/tex]
Step-by-step explanation:
[tex]PREFIXES\\\\mega\ (M)=10^6\\\\kilo\ (k)=10^3\\\\hecto\ (h)=10^2\\\\deko\ (da)=10\\\\decy\ (d)=10^{-1}=0.01\\\\centi\ (c)=10^{-2}=0.01\\\\mili\ (m)=10^{-3}=0.001\\\\mikro\ (\mu)=10^{-6}=0.000001[/tex]
[tex]2\dfrac{1}{100}=2.01\\\\2\dfrac{1}{100}\ km=2.01\ km=2.01\cdot10000\ dm=20100\ dm\\\\1\ kilometers=10000\ decimeters[/tex]
53 pts! which of the following is equal to g(x)?
A. 4^x - 2
B. 4(x - 2)
C. 4^x + 2
D. 4(x+2)
Answer:
B is the correct answer, as x - 2 in the exponent would move the graph to the right 2.
What is 11/6 as a improper fraction
Answer: that is an improper fraction but mixed it’s 1 5/6
Answer:
11/6 as an improper fraction is 1 5/6
Step-by-step explanation:
a local hamburger shop sold a combined total of 637 hamburgers and cheeseburgers on Tuesday.There were 63 fewer cheese burger sole than hamburgers. how many burgers were sold on Tuesday
Answer:
574
Step-by-step explanation:
All your doing is subtracting!
a supplement of an angle is twice as large as the angle. Find the Measure of the angle
let x = the angle
let 2x = supplement of the angle
x + 2x = 180
3x = 180
x = 60
The angles measure is 60 degrees.
Hope this helps!
Expand and combine like terms.
(3c^4-5c^6)^2
Answer:
[tex]9c^{8} -30c^{10} + 25c^{12}[/tex]
Step-by-step explanation:
We can use formula (a-b)² = a² -2ab + b².
In our example a = 3c^4 and b = 5c^6
[tex](3c^{4} - 5c^{6})^{2} = [3c^{4} ]^{2} - 2*3c^{4} *5c^{6} + [5c^{6}]^{2}=\\=9c^{8} -30c^{10} + 25c^{12}[/tex]
Expanding and combining the like terms, the expression becomes [tex]9c^{8} - 30c^{10} + 25c^{12}[/tex] .
How to expand and combine the like terms in the given expression ?Given expression is [tex](3c^{4} - 5c^{6} )^{2}[/tex] .
Using Formula - [tex](a - b)^{2}[/tex] = [tex]a^{2} - 2ab + b^{2}[/tex]
Expanding the expression, we have -
[tex]9c^{8} - 2*3c^{4}*5c^{6} + 25c^{12}[/tex] [Using the above hypothesis]
[tex]9c^{8} - 30c^{10} + 25c^{12}[/tex]
As we can see that there is no like terms or common terms in the expansion of the equation, thus we have the final expression as [tex]9c^{8} - 30c^{10} + 25c^{12}[/tex] .
To learn more about expansion of expression, refer -
https://brainly.com/question/14874506
#SPJ2
The table below shows the numbers of tickets sold at a movie theater on Friday.
NUMBER OF TICKETS SOLD
Day
Adult Tickets
Children's
Tickets
1,678
976
Friday
Saturday
The number of each type of ticket sold on Saturday is described below.
• Adult tickets—2 times as many as the number of adult tickets sold
on Friday
• Children's tickets-3 times as many as the number of children's
tickets sold on Friday
Complete the table above to show the numbers of tickets sold on Saturday.
What is the total number of tickets sold over these two days?
Answer:
Number of Adult's tickets sold on Saturday = 3,356
Number of Children's tickets sold on Saturday = 2, 928
Total number of tickets sold over these two days is 8,938.
Step-by-step explanation:
Here, the number of tickets sold on FRIDAY:
Adult Ticket sold = 1,678
Children's Tickets sold = 976
So, the total number of tickets sold on Friday
= Sum of ( Adult + Children's ) tickets = 1,678 + 976 = 2,654 .... (1)
The number of tickets sold on SATURDAY:
Adult Ticket sold = 2 times as many as the number of adult tickets sold
on Friday
= 1,678 x 2 = 3,356
Children's Tickets sold = 3 times as many as the number of children's
tickets sold on Friday.
= 976 x 3 = 2, 928
So, the total number of tickets sold on Saturday
= Sum of ( Adult + Children's ) tickets = 3,356 + 2,928 = 6, 284 .... (2)
Now, the total number of tickets booked in these two days :
Sum of tickets booked on (Friday + Saturday)
= 2,654 + 6, 284 = 8,938
Hence, total number of tickets sold over these two days is 8,938.
A student wants to write an expression for, "all of the elements which are not in set
A combined with those elements not in set B". Which expression below matches the
statement?
A. (A'NB)
B. (AUB)
C. (A’UB')
D. P(A’ n B’)
Option C. (A’UB') is the correct answer
Step-by-step explanation:
If A and B are two sets
Then
We can say the the elements that are not in set a can only be obtained by finding its complement
So,
all of the elements which are not in set A = A'
Similarly
those elements not in set B = B'
Combining these means that elements of both sets will be : A'UB'
Hence,
Option C. (A’UB') is the correct answer
Keywords: Sets, complements
Learn more about sets at:
brainly.com/question/12973601brainly.com/question/13063819#learnwithBrainly
After a concert for 1,600 people, only 8 people said they would not go to see the band again. What percent of the people who went to the concert said they would not go to see the band again?
Answer:
0.5%
Step-by-step explanation:
8/1600=0.005=0.5%
Answer:
0.5%
explanation:
8/1600=0.005=0.5%
Translate to an algebraic expression: the sum of x and twice y
Answer:
x+2y
20 character minimum
Answer:
The sum of x and twice y
x+2y
5х + 12y — 10 = 0
2x — 3y + 35 = 0
Answer:
(- 10, 5 )
Step-by-step explanation:
Given the 2 equations
5x + 12y - 10 = 0 ( add 10 to both sides )
5x + 12y = 10 → (1)
2x - 3y + 35 = 0 ( subtract 35 from both sides )
2x - 3y = - 35 → (2)
Multiplying (2) by 4 and adding to (1) will eliminate the y- term
8x - 12 y = - 140 (3)
Add (1) and (3) term by term
5x + 8x + 12y - 12y = 10 - 140, that is
13x = - 130 ( divide both sides by 13 )
x = - 10
Substitute x = - 10 into either (1) or (2) and solve for y
Substituting in (1)
5(- 10) + 12y = 10
- 50 + 12y = 10 ( add 50 to both sides )
12y = 60 ( divide both sides by 12 )
y = 5
Solution is (- 10, 5 )
please solve with working! much appreciated
Answer:
i. ) The fraction[tex]\frac{1.7}{1.3}[/tex] as a number with one decimal place is 1.3.
ii. ) The height of the tree is 37.9 m
Step-by-step explanation:
One decimal Place:
Some examples,
4.23 ————————- 4.2
97.456 ———————- 97.5
7324.89456 ————— 7324.9
0.95 ————————- 1.0
76 —————————- 76.0
After the decimal point get rid of all digits but the first 2 If the second digit is more than 4, increase the first digit by 1 Always write the decimal point and one digit even if it is zeroTherefore, the fraction[tex]\frac{1.7}{1.3}[/tex] as a number with one decimal place is 1.3.
ii. )
Given
[tex]\frac{x}{29} =\frac{1.7}{1.3} \\x= 29\times \frac{1.7}{1.3}\\x =\frac{49.3}{1.3}\\x = 37.923....\\x=37.9\ m\ \textrm{rounded to one decimal place}[/tex]
Therefore, the height of the tree is 37.9 m
Noora took $50 out of her savings account each week on Friday. How many weeks ago did she have at least $250 in her account?
Answer:
5 because 250 ÷50 equals 5
Step-by-step explanation:
Because its says she took out 50 each week and you divide by 250 by 50 and 50 represents out of her savings account and which equals 5 because the number of weeks and and she had 250 in there 5 weeks ago and she took 50 out each week so its 5 weeks
The function f(x) = 4x + 8 represents the distance traveled by a herd of elephants in miles. The function g(x) = x − 1 represents the time the herd traveled in hours.
Solve f divided by g of 4, and interpret the answer.
A) 8; the number of elephants in the herd
B)one eighth; the number of elephants in the herd
C)8; the elephants' rate in miles per hour
D)one eighth; the elephants' rate in miles per hour
Answer:C) 8; The elephants’ rate in miles per hour
Step-by-step explanation:
First write the question as an equation that can be solved to give you a numerical answer.
[f(4)=4(4)+8] / [g(4)=(4)-1]
Then solve the equation.
24/3=8
Finally use background information to give you the context.
Since the problem gives you the function for distance and the function for time then it can be concluded that the context will be the elephants’ rate in miles per hour
C is correct i got the answer right on my test :)
Dawn has 5\6 yard of lace. She uses 4\5 of it on a dress and the rest on a jewel box. How much does she use on the jewel box
Answer:
Jewelry box: 1/6 yard
Step-by-step explanation:
4/5 (not 4\5) of her 5/6 yard goes into a dress: (4/5)(5/6 yd) = 2/3 yard.
This is the same as 4/6 yard. The amount of lace remaining, to be used on a jewelry box, is 5/6 - 4/6, or 1/6 yard.
Dawn used 1/6 yard of lace on the jewel box. This was calculated by subtracting the amount of lace used on the dress (2/3 yard) from the total lace available (5/6 yard).
Explanation:The subject of your question pertains to Mathematics, specifically fractions and their applications. To find out how much lace Dawn used on the jewel box, we need to subtract the amount of lace used on the dress from the total amount of lace. Dawn has 5/6 yard of lace and she utilized 4/5 of it on the dress. To find out the part used on the dress in the same unit, multiply the total lace (which is 5/6) by the part used (which is 4/5), so (5/6)*(4/5) = 20/30 or 2/3 yard. To find out what part of the lace was used on the jewel box, subtract the dress lace from the total lace. So, 5/6 - 2/3 gives us 1/6 yard of lace that is used on the jewel box.
Learn more about Fractions here:https://brainly.com/question/10354322
#SPJ2
Goran's gas tank is 1/3
full. After he buys 3 gallons of gas, it is 1/2
full. How many gallons can Goran's tank hold?
Answer: 6 gallons
Step-by-step explanation:
1/3 = 2/6. 1/2 = 3/6
2/6 already + 3/6 = 5/6, it
To determine the total capacity of Goran's gas tank, we set up and solved an algebraic equation, finding that the total capacity of the tank is 18 gallons.
The student's question is about figuring out the total capacity of Goran's gas tank based on the information given. To solve this problem, we can set up a simple algebraic equation based on the proportions of the tank's capacity that are filled. Since filling the tank with 3 gallons of gas takes it from being 1/3 full to 1/2 full, we know that these 3 gallons represent the difference between 1/3 and 1/2 of the tank's total capacity.
Let's denote the total capacity of the tank as 'T' gallons. According to the question:
1/3 of 'T' + 3 gallons = 1/2 of 'T'We can now set up the equation:
1/3 * T + 3 = 1/2 * T
To find 'T', we need to solve for T:
1/2 * T - 1/3 * T = 3
This simplifies to:
(3T - 2T) / 6 = 3
T/6 = 3
Now multiply both sides by 6 to solve for T:
T = 18
Therefore, the total capacity of Goran's gas tank is 18 gallons.